1999
DOI: 10.1017/s0031182099004515
|View full text |Cite
|
Sign up to set email alerts
|

Protease activity in the larval stage of the parasitoid wasp, Eulophus pennicornis (Nees) (Hymenoptera: Eulophidae); effects of protease inhibitors

Abstract: Hymenopteran, parasitoid wasps have good potential for use in integrated pest management (IPM); for example, the gregarious ectoparasitoid, Eulophus pennicornis, has been suggested as a biological control agent for larvae of the tomato moth (Lacanobia oleracea L.). However, the processes by which such parasitic larvae are able to utilize the nutritional resource provided by the host have been little studied. Protease activity was present in E. pennicornis larvae, and characterization of the enzymes responsible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
1
9
0
Order By: Relevance
“…This result showed that the serine proteinases are the major hydrolysing enzymes in the gut of A. rosae. Similar result was reported by Down et al (1999) when they worked on ectoparasitoid Eulophus pennicornis (Hymenoptera: Eulophidae) larvae and concluded that the serine proteinases are the dominant enzymes in the gut of this insect. Also, our results are in agreement with Burgess and Gatehouse (1997) in the presence of serine proteases in gut extracts of the honeybee, Apis mellifera (Hymenoptera: Apidae).…”
Section: Discussionsupporting
confidence: 84%
“…This result showed that the serine proteinases are the major hydrolysing enzymes in the gut of A. rosae. Similar result was reported by Down et al (1999) when they worked on ectoparasitoid Eulophus pennicornis (Hymenoptera: Eulophidae) larvae and concluded that the serine proteinases are the dominant enzymes in the gut of this insect. Also, our results are in agreement with Burgess and Gatehouse (1997) in the presence of serine proteases in gut extracts of the honeybee, Apis mellifera (Hymenoptera: Apidae).…”
Section: Discussionsupporting
confidence: 84%
“…The results of this study suggest that CpTI may have an effect on E pennicornis in terms of its ability to parasitise hosts that have ingested this protein. Although CpTI causes partial inhibition of digestive proteases of wasp larvae in vitro ,43 it is unlikely that the effects reported here are due to direct toxicity. No adverse effects on the wasp were detected when hosts were fed artificial diet containing the inhibitor as opposed to transgenic leaves.…”
Section: Discussionmentioning
confidence: 70%
“…In contrast, the presence of highly expressed S1 serine peptidase genes in embryo and larvae suggest that they may have other putative roles, probably associated with the regulation of growth and development. These physiological processes can potentially be targeted if the protease inhibitors may get access through the mite gut to endogenous targets, as have been already reported in insects [30], [31].…”
Section: Discussionmentioning
confidence: 86%